Dwarfism in homozygous Agc1CreERT mice is associated with decreased expression of aggrecan. Issue 10 (27th September 2017) - Rashid, Harunur; Chen, Haiyan; Hassan, Quamarul; Javed, Amjad
Summary: Aggrecan (Acan), a large proteoglycan is abundantly expressed in cartilage tissue. Disruption of Acan gene causes dwarfism and perinatal lethality of homozygous mice. Because of sustained expression of Acan in the growth plate and articular cartilage, Agc Cre model has been developed for the regulated ablation of target gene in chondrocytes. In this model, the IRES‐CreERT‐Neo‐pgk transgene is knocked‐in the 3′UTR of the Acan gene. We consistently noticed variable weight and size among the Agc Cre littermates, prompting us to examine the cause of this phenotype. Wild‐type, Cre‐heterozygous (Agc +/Cre ), and Cre‐homozygous (Agc Cre/Cre ) littermates were indistinguishable at birth. However, by 1‐month, Agc Cre/Cre mice showed a significant reduction in body weight (18–27%) and body length (19–22%). Low body weight and dwarfism was sustained through adulthood and occurred in both genders. Compared with wild‐type and Agc +/Cre littermates, long bones and vertebrae were shorter in Agc Cre/Cre mice. Histological analysis of Agc Cre/Cre mice revealed a significant reduction in the length of the growth plate and the thickness of articular cartilage. The amount of proteoglycan deposited in the cartilage of Agc Cre/Cre mice was nearly half of the WT littermates. Analysis of gene expression indicates impaired differentiation of chondrocyte in hyaline cartilage of Agc Cre/Cre mice. Notably, both Acan mRNA and protein was reduced by 50% in Agc Cre/Cre mice. A strong correlation was noted between the level of Acan mRNA and the body length. Importantly, Agc +/Cre mice showed no overt skeletal phenotype. Thus to avoid misinterpretation of data, only the Agc +/Cre mice should be used for conditional deletion of a target gene in the cartilage tissue.